The Experts in the Crowd: The Role of Experienced Investors in a Crowdfunding Market1 - Kim, Keongtae; Viswanathan, Siva (MIS Quarterly, 2019)
Using a data set on individual investments in an online crowdfunding platform for mobile applications, this study examines whether an early investor’s experience within the platform serves as a credible signal of quality for other investors in the crowd and, if so, under what conditions. We find that early investors with experience—particularly investors with app development experience and investors with app investment experience—have a disproportionate influence on later investors in the crowd. Investors with app development experience are likely to have better knowledge of the product and are therefore found to be more influential for “concept apps” (apps in the pre-release stage), while investors with app investment experience with a better knowledge of market performance are found to be more influential for “live apps” (apps that are already being sold in the market). Our findings show that the majority of investors in this market, the crowd, although inexperienced, are rather sophisticated in their ability to identify and exploit nüanced differences in the underlying expertise of the early investors, informational signals that align well with the informational needs they face in the different stages of a venture. In examining the ex post performance of apps, we find that apps with investments from investors with experience are positively associated with ex post app sales. More importantly, we find that investors with experience indeed have the ability to select better apps, making their investment choices credible signals of quality for the crowd. Contrary to popular perceptions of crowdfunding platforms as substitutes for traditional expert-dominated mechanisms, our findings indicate that participation by individuals with experience can be beneficial to these markets.